Wykorzystanie wskaźnika P/E w procesie analiz papierów wartościowych - Tarczyński, Waldemar (Utilizing P/E Ratio in Process of Analyses of Securities, 2005)
In the paper the Author proposed an analysis of securities with variable profit, where the P/E ratio is a criterion determining their quality. Essence of the analysis was a research on financial standing of companies within groups obtained with P/E ratio as a criterion of division. Next analysed criterion of division, was a division of companies into companies with high level of P/E ratio, medium level of P/E ratio and low level of P/E ratio. For particular groups synthetic measures of development were calculated, which allow assessment of fundamental strength of companies and groups. Companies quoted on Warsaw Stock Exchange were analysed. Yearly data about financial ratios and P/E ratio was used. The analysed period was 2000-2003.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 126-133